ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT PEGAWAI PEMERINTAH DAERAH DALAM MELAKUKAN TINDAKAN WHISTLEBLOWING STUDI PADA PEMERINTAH DAERAH TIMOR TENGAH UTARA - Maria Ursula Tani’i; Minarni Anaci Dethan (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2022)
This study aims to determine the Organizational Commitment, Personal Cost, Reward, and Attitude of Influence partially and simultaneously on the intentions of local government employees in carrying out whistleblowing actions. This type of research is quantitative descriptive research. Data obtained by distributing questionnaires to 446 respondents. The data analysis technique used is multiple linear analysis. The results of the analysis show (1) Organizational Commitment has no effect on employee intentions to take whistleblowing actions (2) Personal cost affects employee intentions to take whistleblowing actions (3) Rewards do not affect employee intentions to take whistleblowing actions (4) Attitude affects employee intentions to take action whistleblowing (5) Organizational Commitment and Rewards have no significant effect on employees' intentions to take whistleblowing actions and Personal Costs and Attitudes have a significant effect on employees' intentions to take whistleblowing actions.